THE INFLUENCE OF AUDIT COMMITTEE CHARACTERISTICS ON REAL EARNINGS MANAGEMENT - Supriyaningsih, Supriyaningsih; Fuad, Fuad (JURNAL AKUNTANSI DAN AUDITING, 2016)
Â Current study tests the impact of audit committees to the real earnings management.Using the manufacturing public listed companies from Indoensia Stock Exchange from 2012 until 2014, we found that that financial and accounting expertise of audit committee members and audit committee size have positive effect on real earnings management. Furthermore, we also found that the dual positions of the audit committee chairman have a negative effect on earnings management. The Tenure of audit committee chairman however, has no impact on real earnings management.